Comparative efficacy of biodegradable plastic and low density polyethylene mulch on viability of soilborne plant pathogens of strawberry - RAJ, HARENDER (Indian Phytopathology, 2014)
Soil-borne diseases like crown rot (Rhizoctonia solani), southern blight (Sclerotium rolfsii) and wilt (Fusarium oxysporum f. sp. fragariae) are among the important diseases of strawberry. Comparative efficacy of polyethylene and biodegradable mulch was observed in solarization for 40 days in May-June on these pathogens. Biodegradable plastic mulch (BPM) was found slightly less effective with average maximum temperature of 36.9 and 39.1°C in comparison to 38.3 and 40.1°C in low density polyethylene mulch (LDPM) in 2008 and 2009, respectively. Soil solarization with BPM resulted in 96.6, 97.2 and 98.0% reduction in the viability of propagules/sclerotia of F. oxysporum f.sp. fragariae, S. rolfsii and R. solani in comparison to 100% reduction in viability with LDPM at 5 cm soil depth. These pathogens did not survive beyond 40°C in thermal sensitivity test in water bath.